2010
DOI: 10.1213/ane.0b013e3181ce1ffa
|View full text |Cite
|
Sign up to set email alerts
|

Heparin Dose Response Is Independent of Preoperative Antithrombin Activity in Patients Undergoing Coronary Artery Bypass Graft Surgery Using Low Heparin Concentrations

Abstract: BACKGROUND Unfractionated heparin’s primary mechanism of action is to enhance the enzymatic activity of antithrombin (AT). We hypothesized that there would be a direct association between preoperative AT activity and both heparin dose response (HDR) and heparin sensitivity index (HSI) in patients undergoing coronary artery bypass graft surgery. METHODS Demographic and perioperative data were collected from 304 patients undergoing primary coronary artery bypass graft surgery. AT activity was measured after in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 28 publications
4
20
0
1
Order By: Relevance
“…[13,14] In our study, 32 of the 54 patients who developed HR were 65 years old or older, and 52 of these 54 had a platelet count of 300,000 or over. None of our patients who received preoperative heparin were included in the study since the preoperative AT-III activities of these patients were unknown.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…[13,14] In our study, 32 of the 54 patients who developed HR were 65 years old or older, and 52 of these 54 had a platelet count of 300,000 or over. None of our patients who received preoperative heparin were included in the study since the preoperative AT-III activities of these patients were unknown.…”
Section: Discussionmentioning
confidence: 65%
“…None of our patients who received preoperative heparin were included in the study since the preoperative AT-III activities of these patients were unknown. Garvin et al, [14] showed that the preoperative AT-III level did not affect the heparin response but found that preoperative heparin only decreased AT-III activity. However, this decrease did not change the heparin dose response.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Similar to other clinical studies investigating the relationship between AT and heparin responsiveness, we were unable to reproduce the strong positive association that exists in vivo between AT and heparin responsiveness. 10,16 This suggests that decreased heparin response in vivo is multifactorial, and the lack of a strong association between AT activity and heparin responsiveness may be a Table 1 Characteristics of neonates and infants undergoing congenital cardiac surgery…”
Section: Discussionmentioning
confidence: 99%
“…20 In vivo evidence confirms that an AT concentration less than 80% does in fact result in a higher incidence of heparin resistance. However, Garvin et al 23 demonstrated a low correlation, even in patients with an AT concentration less than 80%. However, Garvin et al 23 demonstrated a low correlation, even in patients with an AT concentration less than 80%.…”
Section: Antithrombin-dependent Mechanismmentioning
confidence: 96%